Évaluation des impacts socio-économiques : cas d’unité forestière d’aménagement de la compagnie forestière Leroy-Gabon - Célestine Mengue Medou; Jean-Philippe Waaub (VertigO)
Since the 19th century, the exploitation of the Gabon’s forest resources is centered only on the production of the woody matter. So, the social and environmental impacts are not taken into account during the planning of the forest operations. This work was completed in a management forest unit (FUM) of Leroy-Gabon forest company.  Investigations are carried out in villages and forest camp of this UFA1.  The results show that the social and economical issues and the impacts of the forest exploitation on the village communities and the forest workers. They show also that local populations are not implied in the forest management process.  There are many conflicts between the villagers, the forest company and the forest service.  Health and security of the forest workers are compromised by many factors.